Radiosensitivitas dan Seleksi Mutan Putatif Jeruk Keprok Garut (Citrus reticulata L.) berdasarkan Penanda Morfologi - ,, Karyanti; Purwito, Agus; Husni, Ali (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2015)
ABSTRACTMandarin Citrus cv. garut is a of local citrus variety with several superiority, but not competitive to imported citrus. Quality improvement have been the subject of citrus breeding programme. The objective of this research was to determine lethal dose 50 (LD50) and putative mutans regenerant selected based on morphological markers. Callus was irradiated at doses of 0, 20, 30, 40, 50, 60, 70, 80, 90 and 100 Gy and regenerated through somatic embryogenesis. The result of radiosensitivity showed that lethal dose 50 (LD50) analyzed by Curve Expert 1.4 software was 75.31 Gy. Observation on callus showed variation on morphology and weight of callus. Callus growth was not inhibited at doses 0-50 Gy but at doses 60-100 Gy callus growth was inhibited. Gamma irradiation also affected the formations of somatic embryos. After six weeks on maturation medium, the highest number of embryo somatic was produced from doses of 20 and 100 Gy and following culture on germination medium, the highest number of planlet was produced from doses of 20 and 40 Gy. Based on morphological characters, the selected regenerants had variability of 0-58%.Keywords: gamma irradiation, germination, lethal dosis 50 (LD50), maturation, somatic embryo